Anode for lithium secondary battery, method for producing anode for lithium secondary battery, and lithium secondary battery including anode
A ceramic layer on the silicon-based negative electrode active material layer addresses the volume expansion and gas generation issues in lithium secondary batteries, enhancing battery life and performance by stabilizing the SEI layer and improving lithium distribution.
Patent Information
- Application Number
- JP2024542058
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-05
- Filing Date
- 2023-09-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-09-06
AI Technical Summary
Lithium secondary batteries using silicon-based negative electrode active materials face issues with rapid volume expansion during charging, leading to surface deterioration, gas generation, and reduced battery life due to the destruction and regeneration of the SEI layer, which increases resistance and decreases cycle life.
A ceramic layer with specific thickness and composition is applied on top of the silicon-based negative electrode active material layer to collect and reduce gas generation, stabilize the SEI layer, and improve the uniformity of lithium distribution, thereby enhancing the life characteristics of the battery.
The ceramic layer effectively reduces gas generation, stabilizes the SEI layer, and improves the life characteristics of lithium secondary batteries by maintaining uniform lithium distribution and reducing resistance, resulting in improved capacity retention and performance.
Smart Images

Figure 2025502280000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0113647 filed with the Korean Intellectual Property Office on September 7, 2022, and Korean Patent Application No. 10-2023-0117635 filed with the Korean Intellectual Property Office on September 5, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode for a lithium secondary battery, a method for producing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is power generation and storage using electrochemical reactions.
[0004] At present, a representative example of an electrochemical element that utilizes such electrochemical energy is a secondary battery, and the range of its use is tending to expand more and more.
[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, research into a method for manufacturing a high-density electrode with a higher energy density per unit volume as an electrode for such high-capacity lithium secondary batteries is being actively conducted.
[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.
[0007] In particular, in recent years, in response to the demand for high-density energy batteries, active research has been conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, in the case of high-capacity materials, silicon-based compounds are materials with a large capacity and excellent capacity characteristics compared to conventionally used graphite, but their volume expands rapidly during charging, cutting off the conductive path and reducing battery characteristics, resulting in a decrease in capacity from the beginning. In addition, when silicon-based negative electrodes undergo repeated charge and discharge cycles, lithium ions are not uniformly charged in the depth direction of the negative electrode, and reactions proceed on the surface, accelerating surface deterioration, so performance needs to be improved in terms of battery cycles.
[0008] As mentioned above, silicon-based active materials have a much higher capacity than graphite, which is the most commonly used material in lithium secondary batteries, but the above-mentioned problems cause the process of destruction and regeneration of the SEI layer to continue. This requires the use of more electrolyte to regenerate the SEI layer, which results in the generation of a large amount of gas. When gas is generated, the electrolyte separates the electrodes and the separator, trapping the gas and widening the distance between the positive and negative electrodes, resulting in an increase in local resistance and a rapid reduction in the battery life.
[0009] Therefore, in order to solve the above problems when using silicon-based compounds as negative electrode active materials, various methods are being discussed, such as a method of controlling the driving potential, a method of coating a thin film on the active material layer, a method of controlling the particle size of the silicon-based compound, a method of suppressing the volume expansion itself, or the development of a binder that suppresses the volume expansion of the silicon-based compound to prevent the conductive path from being broken, etc. In addition, research is also being conducted on limiting the usage ratio of silicon-based active materials used during initial charging and discharging through a method of pre-lithiating the silicon-based active material layer, giving it the role of a reservoir, and complementing the life characteristics of the silicon-based negative electrode.
[0010] However, in the case of the above method, the battery performance may be deteriorated, and therefore the application is limited. There is still a limit to the commercialization of the manufacture of negative electrode batteries having a high content of silicon-based compounds. In particular, as the ratio of silicon-based active material contained in the silicon-based active material layer increases, pre-lithiation is concentrated on the surface of the negative electrode, and damage is caused to the silicon-based active material on the surface side, and non-uniform pre-lithiation occurs, resulting in problems in improving the life characteristics.
[0011] Therefore, even when a silicon-based compound is used as an active material, research is needed to find a method for suppressing the amount of gas generation and solving the above problem. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2009-080971 A Summary of the Invention [Problem to be solved by the invention]
[0013] The present application relates to a negative electrode for a lithium secondary battery that can sense generated gases (CO2, H2) and suppress gas generation, which is an existing problem, while using a silicon-based active material in the negative electrode, and can improve the uniformity during pre-lithiation and improve the capacity characteristics and cycle performance of the lithium secondary battery, a method for manufacturing the negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode.
[0014] In order to solve the above problems, the negative electrode for a lithium secondary battery according to the present application solves the above problems by providing a specific ceramic layer on the top of a negative electrode active material layer. [Means for solving the problem]
[0015] One embodiment of the present specification provides a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a ceramic layer provided on the opposite side of the silicon-based negative electrode active material layer to the side facing the negative electrode current collector layer; wherein the ceramic layer comprises a ceramic layer composition or a dried product thereof, the ceramic layer has a thickness of 0.5 μm or more and 10 μm or less, the ceramic layer composition comprises a ceramic and a binder, and contains 10 parts by weight or more and 50 parts by weight or less of BaTiO3 based on 100 parts by weight of the ceramic.
[0016] In yet another embodiment, there is provided a method for producing a negative electrode for a lithium secondary battery, the method including the steps of: preparing a negative electrode current collector layer; applying a negative electrode active material layer composition to one or both sides of the negative electrode current collector layer to form a negative electrode active material layer; and applying a ceramic layer composition to a side of the negative electrode active material layer opposite to the side facing the negative electrode current collector layer to form a ceramic layer, wherein the ceramic layer has a thickness of 0.5 μm or more and 10 μm or less, the ceramic layer composition includes a ceramic and a binder, and contains 10 parts by weight or more and 50 parts by weight or less of BaTiO3 based on 100 parts by weight of the ceramic.
[0017] Finally, there is provided a lithium secondary battery, comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte. Effect of the Invention
[0018] The negative electrode for a lithium secondary battery according to one embodiment of the present invention is characterized by having a silicon-based negative electrode active material layer and a ceramic layer having a specific composition and thickness on the silicon-based negative electrode active material layer, which contains a certain amount of BaTiO3 capable of gas sensing inside the ceramic layer, and is characterized by being able to collect a portion of the gas generated in the silicon-based negative electrode and reduce the amount of gas generated.
[0019] By including the ceramic layer capable of suppressing gas generation as described above, it is possible to suppress an increase in resistance and lithium deposition caused by an increase in the electrode distance due to bubbles being generated between the electrode and the separator and being separated, and it also provides some stability like the SRS layer of the separator, thereby providing an additional stability improvement effect of the battery.
[0020] In addition, the ceramic layer can reduce direct contact points between the silicon-based anode and lithium metal, thereby improving the charge / discharge uniformity of the silicon-based anode and improving performance.
[0021] Furthermore, by having a ceramic layer on the silicon-based negative electrode active material layer, the ceramic layer formed on the separator can be eliminated or minimized, and the thickness of the separator can be reduced, resulting in excellent process and cost characteristics.
[0022] That is, the negative electrode for a lithium secondary battery according to the present application has the advantages of an electrode using a high content of Si particles as a single layer active material, and is characterized by the introduction of a ceramic layer having a specific thickness and composition in order to solve the problems of surface deterioration, uniformity during pre-lithiation, and life characteristics due to gas generation, which are disadvantages of the electrode using a single layer active material. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Before describing the present invention, some terms will first be defined.
[0025] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0026] In this specification, "p to q" means a range of "not less than p and not more than q".
[0027] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the above-mentioned measurement method.
[0028] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at the 50% point of the cumulative particle number distribution by particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution by particle size. Meanwhile, the particle size distribution can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam is measured to calculate the particle size distribution.
[0029] In this specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer is involved in a polymerization reaction and is contained as a repeating unit in the polymer. In this specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.
[0030] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless otherwise specified as a "homopolymer."
[0031] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various polymerization degrees that are commercially available for molecular weight measurement as standard substances. In this specification, the molecular weight means the weight average molecular weight unless otherwise specified.
[0032] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings in order to enable those skilled in the art to easily carry out the present invention. However, the present invention may be embodied in many different forms and is not limited to the following description.
[0033] One embodiment of the present specification provides a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a ceramic layer provided on the opposite side of the silicon-based negative electrode active material layer to the side facing the negative electrode current collector layer; wherein the ceramic layer comprises a ceramic layer composition or a dried product thereof, the ceramic layer has a thickness of 0.5 μm or more and 10 μm or less, the ceramic layer composition comprises a ceramic and a binder, and contains 10 parts by weight or more and 50 parts by weight or less of BaTiO3 based on 100 parts by weight of the ceramic.
[0034] The negative electrode for a lithium secondary battery according to the present application is characterized by the introduction of a ceramic layer having a specific thickness and composition in order to obtain the advantages of an electrode using a high content of Si particles as a single layer active material, while resolving the disadvantages of having such an electrode, such as the problems of surface deterioration, the problem of uniformity during pre-lithiation, and the problems of life characteristics associated with gas generation.
[0035] 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a negative electrode active material layer 20 and a ceramic layer 10 on one side of a negative electrode current collector layer 30 can be seen. Although FIG. 1 shows that the negative electrode active material layer is formed on one side, it may be formed on both sides of the negative electrode current collector layer.
[0036] The negative electrode for a lithium secondary battery of the present invention will be described in more detail below.
[0037] The present application provides a negative electrode for a lithium secondary battery, the negative electrode comprising: a negative electrode current collector layer; a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a ceramic layer provided on a surface of the silicon-based negative electrode active material layer opposite to the surface facing the negative electrode current collector layer.
[0038] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the binding force of the negative electrode active material can be strengthened by forming fine irregularities on the surface, and it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0039] In one embodiment of the present application, the negative electrode current collector layer may have a thickness of 1 μm or more and 100 μm or less.
[0040] However, the thickness may vary depending on the type and application of the negative electrode used, and is not limited thereto.
[0041] In one embodiment of the present application, the silicon-based negative electrode active material layer contains a negative electrode active material layer composition, and the negative electrode active material layer composition includes at least one selected from the group consisting of a silicon-based active material, a negative electrode conductive material, and a negative electrode binder, and provides a negative electrode for a lithium secondary battery.
[0042] In one embodiment of the present application, the silicon-based active material may include at least one selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys.
[0043] In one embodiment of the present application, the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more.
[0044] In another embodiment, the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x ≤ 2), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more.
[0045] In another embodiment, based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be included in an amount of 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0046] In one embodiment of the present application, particularly pure silicon (Si) may be used as the silicon-based active material. Using particularly pure silicon (Si) as the silicon-based active material means that, as described above, when based on a total of 100 parts by weight of the silicon-based active material, pure Si particles (SiOx (x = 0)) not bonded to other particles or elements are included within the above range.
[0047] In one embodiment of the present application, the silicon-based active material may consist of SiOx (x=0).
[0048] Silicon-based active materials have a significantly higher capacity than the graphite-based active materials that have been used conventionally, and there have been increasing efforts to use them. However, because of their high volume expansion during charging and discharging, they have only been used in small amounts mixed with graphite-based active materials.
[0049] The negative electrode active material layer according to the present application contains a silicon-based active material, specifically, pure silicon particles containing 70 parts by weight or more of SiOx (x=0). In this case, when the pure silicon particles are contained in a high content, the capacitance characteristics are excellent, and in order to solve the life reduction characteristics due to the surface non-uniform reaction, the above problem is solved by including the ceramic layer according to the present invention.
[0050] In one embodiment of the present application, the crystal grain size of the silicon-based active material may be 200 nm or less.
[0051] In another embodiment, the crystal grain size of the silicon-based active material may be 200 nm or less, preferably 130 nm or less, more preferably 110 nm or less, even more preferably 100 nm or less, specifically 95 nm or less, more specifically 91 nm or less. The crystal grain size of the silicon-based active material may be in the range of 10 nm or more, preferably 15 nm or more.
[0052] The silicon-based active material has the above-mentioned crystal grain size, and the crystal grain size of the silicon-based active material can be adjusted by changing the process conditions in the manufacturing process. In this case, by satisfying the above-mentioned range, the grain boundaries are widely distributed, and lithium ions are uniformly inserted during insertion, and the stress applied when lithium ions are inserted into silicon particles can be reduced, thereby alleviating particle cracking. As a result, the negative electrode has the characteristic of improving the life stability. If the crystal grain size exceeds the above-mentioned range, the grain boundaries within the particles are narrowly distributed, and in this case, lithium ions are non-uniformly inserted within the particles, and the stress due to ion insertion is large, resulting in particle cracking.
[0053] In one embodiment of the present application, the silicon-based active material may include a crystalline structure having a crystal grain distribution of 1 nm or more and 200 nm or less, and the area ratio of the crystalline structure may be 5% or less based on the total area of the silicon-based active material.
[0054] In still another embodiment, the area ratio of the crystalline structure may be 5% or less, 3% or less, or 0.1% or more, based on the total area of the silicon-based active material.
[0055] That is, the silicon-based active material according to the present application has a crystal grain size of 200 nm or less, and the size of each crystal structure is small, so that the above-mentioned area ratio can be satisfied, and thus the distribution of the grain boundaries can be broadened, thereby achieving the above-mentioned effects.
[0056] In one embodiment of the present application, the silicon-based active material may contain 20 or more crystal structures.
[0057] In another embodiment, the number of crystalline structures contained in the silicon-based active material may be 20 or more, 30 or more, or 35 or more, and may be in the range of 60 or less, or 50 or less.
[0058] That is, as described above, when the silicon-based active material has a crystal grain size that satisfies the above range and the number of crystal structures that satisfies the above range, the strength of the silicon-based active material itself will have an appropriate range, and when contained in an electrode, it will be able to provide flexibility and have the characteristic of being able to efficiently suppress volume expansion.
[0059] In this application, the term "crystal grain" refers to a crystal grain in a metal or material that is an aggregate of microscopic irregular shapes, and the term "crystal grain size" can refer to the diameter of the observed crystal grain. That is, in this application, the term "crystal grain size" refers to the size of a domain that shares the same crystal orientation within a grain, and has a different concept from the grain size or particle size that represents the size of a substance.
[0060] In one embodiment of the present application, the crystal grain size can be calculated as a FWHM (Full Width at Half Maximum) value through XRD analysis. The remaining values except L are measured through XRD analysis of a silicon-based active material, and the crystal grain size can be measured according to the Debye-Scherrer equation, which shows that FWHM and crystal grain size are inversely proportional to each other. In this case, the Debye-Scherrer equation is as shown in the following Equation 1-1.
[0061] [Formula 1-1] FWHM=Kλ / LCosθ
[0062] In the above formula 1-1, L is the grain size, K is a constant, θ is the Bragg angle, and λ is the wavelength of X-ray.
[0063] The crystal grains have various shapes and can be measured three-dimensionally. Generally, the size of the crystal grains can be measured by commonly used circle method and diameter measurement method, but is not limited thereto.
[0064] The diameter measurement method involves drawing 5 to 10 equilibrium lines, each with a length of L mm, on a micrograph of the target particle, counting the number of crystal grains z on the lines, and averaging them. At this time, only those that are completely contained are counted, and those that are overlapping are excluded. If the number of lines is P and the magnification is V, the average particle diameter can be calculated using the following formula 1-2.
[0065] [Formula 1-2] Dm = (L*P*10 3 ) / (zV)(um)
[0066] In addition, the circle method involves drawing a circle of a specified diameter on a micrograph of the target particle, and then calculating the average area of the crystal grains from the number of crystal grains that fall within the circle and the number of crystal grains that cross the boundary line, and can be calculated using the following formula 1-3.
[0067] [Formula 1-3] Fm = (Fk * 10 6 ) / ((0.67n+z)V 2 )(um 2 )
[0068] In the above formula 1-3, Fm is the average particle area, Fk is the measured area on the photograph, z is the number of particles that fit inside the circle, n is the number of particles that span the arc, and V is the magnification of the microscope.
[0069] In one embodiment of the present application, the silicon-based active material has a surface area of 0.25 m 2 / g or more.
[0070] In yet another embodiment, the silicon-based active material has a surface area of 0.25 m 2 / g or more, preferably 0.28m 2 / g or more, more preferably 0.30m 2 / g or more, specifically 0.31m 2 / g or more, more specifically 0.32m 2 The silicon-based active material may have a surface area of 3 m 2 / g or less, preferably 2.5m 2 / g or less, more preferably 2.2m 2 The following ranges can be satisfied: / g. The surface area can be determined (using nitrogen) according to DIN 66131:
[0071] The silicon-based active material has the above surface area, and the size of the surface area of the silicon-based active material can be adjusted by changing the process conditions in the manufacturing process and the growth conditions of the silicon-based active material. That is, when the silicon-based active material is manufactured by the manufacturing method according to the present application, it has a larger surface area than particles having the same particle size due to the rough surface, and in this case, it has the characteristic that it can reduce cracks in the electrode caused by repeated charge and discharge cycles by satisfying the above range and increasing the binding force with the binder.
[0072] In addition, lithium ions are inserted uniformly during insertion, so that the stress applied when lithium ions are inserted into silicon particles can be reduced, and thus particle cracking can be alleviated. As a result, the negative electrode has the characteristic of improving its life stability. If the surface area size is less than the above range, even if the particles have the same particle size, the surface is formed smoothly, and the binding force with the binder is reduced, causing electrode cracks. In this case, lithium ions are inserted non-uniformly within the particles, and the stress caused by ion insertion is large, causing particle cracking.
[0073] In one embodiment of the present application, the silicon-based active material satisfies the range of the following formula 2-1. [Formula 2-1] X1 / Y1≦0.960
[0074] In the above formula 2-1, X1 is the actual area of the silicon-based active material, Y1 means the area of a spherical particle having the same circumference as the silicon-based active material.
[0075] The formula 2-1 can be measured using a particle analyzer. Specifically, the silicon-based active material according to the present application is scattered on a glass plate by injecting air, and then a shadow image of the scattered silicon-based active material particles is photographed to measure the shapes of 10,000 silicon-based active material particles in the photograph. In this case, the formula 2-1 is a value representing the average for 10,000 particles. The formula 2-1 according to the present application can be measured from the image, and the formula 2-1 can be expressed as the circularity of the silicon-based active material. The circularity is calculated as [4π*actual area of silicon-based active material / (boundary) 2 ] may also be expressed as:
[0076] In one embodiment of the present application, the sphericity of the silicon-based active material may be, for example, 0.960 or less, for example, 0.957 or less. The sphericity of the silicon-based active material may be, for example, 0.8 or more, for example, 0.9 or more, specifically 0.93 or more, more specifically 0.94 or more, for example, 0.941 or more.
[0077] In one embodiment of the present application, the silicon-based active material satisfies the range of the following formula 2-2.
[0078] [Formula 2-2] X2 / Y2≦0.995
[0079] In the above formula 2-2, Y2 is the actual perimeter of the silicon-based active material, X2 is the perimeter of the circumscribing figure of the silicon-based active material.
[0080] The formula 2-2 can be measured using a particle analyzer. Specifically, the silicon-based active material according to the present application is scattered on a glass plate by air injection, and then a shadow image of the scattered silicon-based active material particles is photographed to measure the shapes of 10,000 silicon-based active material particles in the photograph. In this case, the formula 2-2 is a value representing the average for 10,000 particles. The formula 2-2 according to the present application can be measured from the image, and the formula 2-2 can be expressed as the convexity of the silicon-based active material.
[0081] In one embodiment of the present application, the range of X2 / Y2≦0.996, preferably X2 / Y2≦0.995, may be satisfied, and the range of 0.8≦X2 / Y2, preferably 0.9≦X2 / Y2, more preferably 0.95≦X2 / Y2, specifically 0.98≦X2 / Y2 may be satisfied.
[0082] The smaller the value of the formula 2-1 or 2-2, the greater the roughness of the silicon-based active material. By using a silicon-based active material having the above range, the bonding strength with the binder is increased, and thus cracks in the electrode caused by repeated charge / discharge cycles can be alleviated.
[0083] In one embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less.
[0084] The silicon-based active material containing silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less means that the material contains a large number of individual silicon-based particles having a particle size within the range, and the number of silicon-based particles contained is not limited.
[0085] The particle size of the silicon-based particles may be expressed as a diameter when the particles are spherical, but when the particles are non-spherical in shape, the particle size may be measured in comparison with the spherical shape, and the particle size of individual silicon-based particles may be measured by a method generally used in the art.
[0086] On the other hand, the average particle size (D50) of the silicon-based active material of the present invention may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is less than 5 μm, the specific surface area of the particles increases excessively, and the viscosity of the negative electrode slurry increases too much. As a result, the particles constituting the negative electrode slurry are not dispersed smoothly. In addition, when the size of the silicon-based active material is too small, the contact area between the silicon particles and the conductive material is reduced due to the complex of the conductive material and the binder in the negative electrode slurry, so that the conductive network is more likely to be cut, and the capacity retention rate decreases. On the other hand, when the average particle size exceeds 10 μm, the silicon particles are too large, and the surface of the negative electrode cannot be made smooth, which causes current density unevenness during charging and discharging. In addition, when the silicon particles are too large, the phase stability of the negative electrode slurry becomes unstable, and the processability decreases. As a result, the capacity retention rate of the battery decreases.
[0087] In one embodiment of the present application, the silicon-based active material generally has a characteristic BET surface area. The BET surface area of the silicon-based electrode active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET surface area is determined according to DIN 66131 (using nitrogen).
[0088] In one embodiment of the present application, silicon-based active material can be, for example, in crystalline or amorphous form, and is preferably not porous.Silicon particles are preferably spherical or shard particles.Alternatively, but less preferably, silicon particles can have a fibrous structure or be in the form of silicon-containing film or coating.
[0089] In one embodiment of the present application, the negative electrode composition includes 70 parts by weight or more of the silicon-based active material based on 100 parts by weight of the negative electrode active material layer composition.
[0090] In another embodiment, the silicon-based active material may be included in an amount of 70 parts by weight or more, preferably 75 parts by weight or more, more preferably 80 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and may be included in an amount of 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less.
[0091] The negative electrode active material layer composition according to the present application uses a silicon-based active material with a remarkably high capacity within the above range, and by using a ceramic layer described later in combination, the capacity performance of the entire negative electrode is not reduced, and the problems of surface deterioration during charging and discharging, uniformity during pre-lithiation, and gas generation are solved. In addition, by using a specific negative electrode conductive material and a negative electrode binder that can suppress the volume expansion rate during charging and discharging, the negative electrode performance is not reduced even when the above range is included, and the output characteristics during charging and discharging are excellent.
[0092] In one embodiment of the present application, the silicon-based active material may have a non-spherical morphology, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0093] In this application, the circularity is determined by the following formula 1, where A is the area and P is the perimeter. [Formula 1] 4πA / P 2
[0094] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but in recent years, as the demand for high-capacity batteries has increased, attempts to mix and use silicon-based active materials to increase capacity have been increasing. However, in the case of silicon-based active materials, even if the properties of the silicon-based active materials themselves are adjusted as described above, there may be some problems in that the volume of the silicon-based active materials rapidly expands during charging / discharging, damaging the conductive path formed in the negative electrode active material layer.
[0095] Therefore, in one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode active material layer composition comprises at least one selected from the group consisting of a negative electrode conductive material; and a negative electrode binder.
[0096] In one embodiment of the present application, the negative electrode conductive material may include at least one selected from the group consisting of a dot-like conductive material, a sheet-like conductive material, and a linear conductive material.
[0097] In one embodiment of the present application, the dot-shaped conductive material means a spherical or dot-shaped conductive material that can be used to improve the conductivity to the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-shaped conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and may preferably include carbon black in that it realizes high conductivity and has excellent dispersibility.
[0098] In one embodiment of the present application, the dot-shaped conductive material has a BET specific surface area of 40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.
[0099] In one embodiment of the present application, the dotted conductive material may have a functional group content (volatile matter) of 0.01% or more and 1% or less, preferably 0.01% or more and 0.3% or less, and more preferably 0.01% or more and 0.1% or less.
[0100] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, functional groups are present on the surface of the dot-shaped conductive material, and when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent.
[0101] In one embodiment of the present application, the active material is characterized in that it contains a dot-shaped conductive material having a functional group content in the above range together with a silicon-based active material, and the functional group content can be adjusted depending on the degree of heat treatment of the dot-shaped conductive material.
[0102] That is, in the production of the point-like conductive material, a high functional group content can mean that there is a lot of foreign matter, and a low functional group content can mean that more heat treatment processing has been performed.
[0103] In one embodiment of the present application, the particle diameter of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0104] In one embodiment of the present application, the negative electrode conductive material may include a sheet conductive material.
[0105] The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode, and at the same time, can suppress the disconnection of the conductive path due to volume expansion, and can be expressed as a plate-type conductive material or a bulk-type conductive material.
[0106] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may be preferably platelet graphite.
[0107] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. If the range is satisfied, the sufficient particle size makes it easy to disperse without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersing using the same device and time, the dispersion effect is excellent.
[0108] In one embodiment of the present application, the sheet conductive material may have a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.
[0109] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.
[0110] In one embodiment of the present application, the sheet conductive material may be a high-specific surface area sheet conductive material or a low-specific surface area sheet conductive material without any restrictions. However, the sheet conductive material in the present application may be affected to some extent by dispersion in terms of electrode performance, and it may be particularly preferable to use a low-specific surface area sheet conductive material that does not cause dispersion problems.
[0111] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more.
[0112] In another embodiment, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m2 / g or more 250m 2 / g or less.
[0113] In another embodiment, the sheet conductive material is a high specific surface area sheet conductive material having a BET specific surface area of 50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.
[0114] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of 5 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.
[0115] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. The bundled carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in the form of a bundle or rope in which a plurality of carbon nanotube units are arranged in a line with the longitudinal axes of the carbon nanotube units substantially aligned in the same direction or are entangled. The carbon nanotube units have a graphite sheet with a nano-sized diameter and a cylindrical shape with an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure of the graphite sheet. The bundled carbon nanotubes can be uniformly dispersed during the manufacture of the negative electrode compared to entangled type carbon nanotubes, and can smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0116] In one embodiment of the present application, the linear conductive material may include SWCNTs; or MWCNTs.
[0117] In one embodiment of the present application, there is provided a negative electrode composition in which the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.
[0118] In another embodiment, the negative electrode conductive material may be included in an amount of 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 10 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0119] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, the negative electrode conductive material comprising a sheet conductive material and a linear conductive material, the sheet conductive material being contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less based on 100 parts by weight of the negative electrode conductive material.
[0120] In another embodiment, the sheet conductive material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 99.9 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0121] In another embodiment, the amount of the linear conductive material may be 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 10 parts by weight or less, and more preferably 0.1 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0122] In particular, in one embodiment of the present application, the negative electrode conductive material includes a planar conductive material and a linear conductive material, each of which satisfies the above-mentioned composition and ratio, so that the battery does not have a significant effect on the life characteristics of existing lithium secondary batteries, there are more points at which charging and discharging are possible, and the battery has excellent output characteristics at a high C-rate.
[0123] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application serves to capture the contact between the silicon-based active materials, which have a very large volume expansion of the electrodes due to charging and discharging, while the positive electrode conductive material serves to impart some conductivity while acting as a buffer having a shock-absorbing function when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.
[0124] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.
[0125] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and a role different from those of the carbon-based active material generally used as a conventional negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dotted shape to facilitate the storage and release of lithium ions.
[0126] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape and can be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not play a role in storing and releasing lithium, but means a material for securing a planar conductive path inside the negative electrode active material layer.
[0127] That is, in the present application, the use of plate-shaped graphite as a conductive material means that it is processed into a planar or plate-shaped form and used as a material to ensure a conductive path, rather than to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and plays a role in storing and releasing all the lithium ions transferred from the positive electrode.
[0128] Meanwhile, in the present application, the use of a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material that plays a role in storing or releasing lithium.
[0129] That is, in one embodiment of the present application, the carbon-based active material, artificial graphite or natural graphite, is dot-shaped and has a BET specific surface area of 0.1 m 2 / g or more 4.5m 2 / g or less. The plate-shaped graphite, which is a planar conductive material, may be planar and have a BET specific surface area of 5 m 2 / g or more.
[0130] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0131] The negative electrode binder according to one embodiment of the present application plays a role in suppressing the active material and conductive material in order to prevent twisting and structural deformation of the negative electrode structure during volume expansion and relaxation of the silicon-based active material, and any common binder can be used as long as it fulfills the above role, and specifically, a water-based binder can be used, and more specifically, a PAM-based binder can be used.
[0132] In one embodiment of the present application, the amount of the negative electrode binder is 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the negative electrode composition, and may be 5 parts by weight or more, or 10 parts by weight or more.
[0133] In particular, the negative electrode binder according to the present application uses a water-based binder due to the use of a silicon-based active material with high rigidity. The water-based binder is a polymer that exhibits very high rigidity after drying. When the water-based binder is included in the negative electrode active material layer composition according to the present application, if a ceramic layer made of a water-based material is coated on the top of the silicon-based negative electrode active material layer made of a water-based material and then dried, the surface will be mixed with water and inter-mixing will occur no matter how quickly it is dried. In order to solve the above problems, the ceramic layer according to the present application uses an organic binder and an organic solvent, and the ceramic and organic binder can be easily dispersed without affecting the negative electrode made of a water-based material, and has the characteristic of being able to form a very dense coating on the negative electrode active material layer.
[0134] In one embodiment of the present application, the negative electrode active material layer further includes a ceramic layer provided on a surface of the silicon-based negative electrode active material layer opposite to the surface facing the negative electrode current collector layer.
[0135] As described above, the negative electrode for a lithium secondary battery according to the present application includes a ceramic layer, and by including the above-mentioned negative electrode active material, it maintains high capacity and high density characteristics, while resolving the problems of surface deterioration during charging and discharging, the problem of uniformity during pre-lithiation, and the problem of life characteristics due to gas generation.
[0136] Specifically, the main reason gas is generated in Si-based negative electrodes is that the SEI layer is destroyed and re-formed due to the large volume expansion / contraction of the Si active material. In other words, the SEI layer is continuously destroyed and re-formed, and when the particles are crushed due to deep use of Si, a new Si surface is formed, and an additional reaction occurs to form a new SEI layer. This generates gas, which acts as resistance between the electrodes and causes performance degradation. To solve this problem, a ceramic layer, which will be described later, is used on top of the negative electrode active material layer.
[0137] In one embodiment of the present application, the ceramic layer may comprise a ceramic layer composition or a dried product thereof.
[0138] In this case, "including the ceramic layer composition" may mean that the ceramic layer includes the ceramic layer composition as it is, and "including the dried product of the ceramic layer composition" may mean that all of the organic solvent that may be included in the ceramic layer composition is removed after drying and is not included in the ceramic layer.
[0139] In one embodiment of the present application, the ceramic layer may have a thickness of 0.5 μm or more and 10 μm or less.
[0140] In another embodiment, the thickness of the ceramic layer may be 0.5 μm or more and 8 μm or less, preferably 2 μm or more and 6 μm or less.
[0141] As described above, when the thickness of the ceramic layer satisfies the above range, the effect of improving stability by controlling the rate of prelithiation during prelithiation can be obtained. If the thickness of the ceramic layer exceeds the above range, problems such as deterioration of the performance of the negative electrode may occur, and the efficiency during prelithiation may be reduced. Also, if the thickness of the ceramic layer is less than the above range, it is difficult to control the rate of prelithiation, and problems such as shortened life due to electrode deterioration caused by surface reaction on the upper part of the negative electrode active material layer may occur.
[0142] It was also confirmed that by satisfying the above range, the gas adsorption characteristics are particularly excellent.
[0143] In one embodiment of the present application, the ceramic layer composition may include a ceramic and a binder, and the ceramic may include 10 parts by weight or more and 50 parts by weight or less of BaTiO3 based on 100 parts by weight of the ceramic.
[0144] More specifically, the ceramic may contain 10 parts by weight or more and 50 parts by weight or less, preferably 15 parts by weight or more and 40 parts by weight or less, and more preferably 20 parts by weight or more and 35 parts by weight or less, of BaTiO3, based on 100 parts by weight of the ceramic.
[0145] In one embodiment of the present application, the ceramic can be used without limitation as long as it can function as the ceramic layer. Specifically, the ceramic can be Al2O3, ZrO2, SiO 2、 The present invention provides a negative electrode for a lithium secondary battery, which contains one or more materials selected from the group consisting of TiO2, ZnO, BaTiO3, SrTiO3, CaCO3, CaO, CeO2, NiO, MgO, SnO2, Y2O3, Pb(Zr,Ti)O3 (PZT), (Pb,La)(Zr,Ti)O3 (PLZT), PB(Mg3Nb2 / 3)O3-PbTiO3 (PMN-PT) and hafnia (HfO2).
[0146] As described above, the ceramic can be any of various ceramics without limitation, and is characterized by including BaTiO3 in the above weight parts. By including the above weight parts of ceramic, the battery has BaTiO3, which has the most effective structure for containing gas generated at the anode, and has excellent gas adsorption properties, and can further include other ceramics to play the role of a buffer layer.
[0147] In one embodiment of the present application, the ceramic contains BaTiO3 and Al2O3, and contains BaTiO3 in an amount of 10 parts by weight or more and 50 parts by weight or less based on 100 parts by weight of the ceramic.
[0148] Specifically, the ceramic contains BaTiO3 and Al2O3 and can satisfy a weight ratio of BaTiO3:Al2O3=80:20.
[0149] In one embodiment of the present application, the ceramic layer composition may further include a solvent, in which case the solvent may be completely removed when the ceramic layer is formed.
[0150] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the solvent includes at least one selected from the group consisting of N-methylpyrrolidone (NMP); dimethylformamide (DMF); acetone; and dimethylacetamide.
[0151] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the binder is polyvinylidene fluoride (PVdF); or polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP).
[0152] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which a surface of the ceramic layer opposite to the surface facing the negative electrode active material layer is joined to lithium metal, and then the surface is allowed to stand at 23°C for 10 seconds to 2 minutes, and the adhesive strength is 10 gf / 15 mm or more and 100 gf / 15 mm or less.
[0153] The adhesive strength was measured at 90° and a speed of 5 mm / s using a peel strength tester with 3M 9070 tape. Specifically, one side of the lithium metal layer of the negative electrode, in which the lithium metal layer is laminated on the top of the ceramic layer, was attached to one side of a slide glass (3M 9070 tape) to which an adhesive film was attached. Then, the adhesive was attached by reciprocating 5 to 10 times with a 2 kg rubber roller, and the adhesive strength (peel strength) was measured at an angle of 90° and a speed of 5 mm / s. In this case, the adhesive strength can be measured under conditions of 23°C and normal pressure.
[0154] In one embodiment of the present application, normal pressure may mean pressure in a state where no specific pressure is applied or reduced, and may be used in the same sense as atmospheric pressure. Generally, it may be expressed as 1 atmosphere.
[0155] In one embodiment of the present application, the adhesive strength after joining a surface of the ceramic layer opposite to the surface facing the negative electrode active material layer to lithium metal and leaving the surface at 23° C. for 10 seconds to 2 minutes may be 10 gf / 15 mm or more and 100 gf / 15 mm or less, preferably 15 gf / 15 mm or more and 95 gf / 15 mm or less, and more preferably 20 gf / 15 mm or more and 50 gf / 15 mm or less.
[0156] As described above, when the adhesive strength between the ceramic layer and lithium metal satisfies the above range, the adhesive strength between the lithium metal and the ceramic layer is good and transferability is ensured when transferring the lithium metal using the transfer process of the pre-lithiation process, and problems such as reverse transfer do not occur, allowing the pre-lithiation process to proceed smoothly.
[0157] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising 60 parts by weight or more and 95 parts by weight or less of the ceramic and 5 parts by weight or more and 40 parts by weight or less of the binder, based on 100 parts by weight of the ceramic layer composition.
[0158] In this case, the organic solvent contained in the ceramic layer composition does not correspond to an effective material, and the reference of 100 parts by weight of the ceramic layer composition may refer to the parts by weight including only the ceramic and the binder.
[0159] In one embodiment of the present application, the ceramic may be present in an amount of 60 parts by weight or more and 95 parts by weight or less, preferably 65 parts by weight or more and 90 parts by weight or less, and more preferably 70 parts by weight or more and 90 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.
[0160] In one embodiment of the present application, based on 100 parts by weight of the ceramic layer composition, the binder may be present in an amount of 5 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 35 parts by weight or less, and more preferably 10 parts by weight or more and 30 parts by weight or less.
[0161] As described above, since the ceramic layer composition contains the binder and ceramic in the containing portion, the dispersibility of the binder and ceramic is improved and they are uniformly formed in the ceramic layer, so that the prelithiation rate can be smoothly controlled, and the coating density during coating of the ceramic layer can be improved by satisfying an appropriate viscosity range.
[0162] In one embodiment of the present application, the negative electrode active material layer may have a thickness of 10 μm to 200 μm.
[0163] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be a pre-lithiated negative electrode.
[0164] In one embodiment of the present application, there is provided a method for producing a negative electrode for a lithium secondary battery, the method including the steps of: preparing a negative electrode current collector layer; applying a negative electrode active material layer composition to one or both sides of the negative electrode current collector layer to form a negative electrode active material layer; and applying a ceramic layer composition to a side of the negative electrode active material layer opposite to the side facing the negative electrode current collector layer to form a ceramic layer; wherein the ceramic layer has a thickness of 0.5 μm or more and 10 μm or less, the ceramic layer composition includes a ceramic and a binder, and contains 10 parts by weight or more and 50 parts by weight or less of BaTiO3 based on 100 parts by weight of the ceramic.
[0165] In the method for preparing the negative electrode, the composition and content of each step may be the same as those described above.
[0166] In one embodiment of the present application, a negative electrode active material layer composition is applied to one or both surfaces of the negative electrode current collector layer to form a negative electrode active material layer.
[0167] That is, the step of forming a negative electrode active material layer on a negative electrode current collector layer may refer to a step of forming an active material layer on a surface opposite to the current collector layer.
[0168] In one embodiment of the present application, applying the negative electrode active material layer composition includes applying and drying a negative electrode slurry including the negative electrode active material layer composition; and a negative electrode slurry solvent.
[0169] In this case, the solid content of the negative electrode slurry may be in the range of 10% to 40%.
[0170] In one embodiment of the present application, the step of forming the negative electrode active material layer may include the steps of mixing the negative electrode slurry; and coating one or both sides of the negative electrode current collector layer with the mixed negative electrode slurry, and the coating may be performed using a coating method commonly used in the art.
[0171] Thereafter, in one embodiment of the present application, a ceramic layer composition is applied to a surface of the negative active material layer opposite to the surface facing the negative current collector layer to form a ceramic layer.
[0172] In one embodiment of the present application, there is provided a method for producing a negative electrode for a lithium secondary battery, comprising the steps of applying the ceramic layer composition, and then drying and rolling the applied ceramic layer composition to remove an organic solvent from the ceramic layer composition.
[0173] In one embodiment of the present application, the negative electrode slurry solvent may be used without limitation as long as it can dissolve and disperse the negative electrode active material layer composition, and specifically, water or NMP may be used.
[0174] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, the method including a step of pre-lithiating a negative electrode in which a negative electrode active material layer and a ceramic layer are formed on the negative electrode current collector, the step of pre-lithiating the negative electrode including a lithium electrolytic plating process; a lithium metal transfer process; a lithium metal deposition process; or a stabilized lithium metal powder (SLMP) coating process.
[0175] The negative electrode for a lithium secondary battery as described above includes SiOx (x=0) as a negative active material layer for enhancing capacity characteristics, and the ceramic layer has the specific composition and thickness described above, so that it can provide the advantage of fast charging. That is, compared to the case where only a negative active material layer is applied, the ceramic layer has the above composition, so that a uniform pre-lithiation process can be performed on the upper end of the negative electrode, and thus the life span can be further improved.
[0176] In one embodiment of the present application, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less.
[0177] In another embodiment, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0178] The porosity varies depending on the composition and content of the silicon-based active material, the negative electrode conductive material, and the negative electrode binder contained in the negative electrode active material layer, and is characterized in that the electrode has an appropriate range of electrical conductivity and resistance.
[0179] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0180] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.
[0181] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0182] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0183] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.6); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.6) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.
[0184] In one embodiment of the present application, the positive electrode active material includes a lithium transition metal composite compound including nickel (Ni), cobalt (Co), and manganese (Mn), and the lithium transition metal composite compound includes single particles or secondary particles, and the average particle size (D50) of the single particles may be 1 μm or more.
[0185] For example, the average particle size (D50) of the single particles may be 1 μm or more and 12 μm or less, 1 μm or more and 8 μm or less, 1 μm or more and 6 μm or less, more than 1 μm and 12 μm or less, more than 1 μm and 8 μm or less, or more than 1 μm and 6 μm or less.
[0186] The single particle can have excellent particle strength even if it is formed with a small particle size having an average particle size (D50) of 1 μm or more and 12 μm or less. For example, the single particle can have a strength of 650 kgf / cm 2 When the particle is rolled with a force of 650 kgf / cm, the particle strength is 100 MPa to 300 MPa. 2 Even if the electrode is rolled with a strong force, the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, thereby improving the life characteristics of the battery.
[0187] The single particles may be prepared by mixing a transition metal precursor and a lithium source material and sintering the mixture. The secondary particles may be prepared by a method different from that of the single particles, and the composition of the secondary particles may be the same as or different from that of the single particles.
[0188] The method for forming the single particles is not particularly limited, but generally, the particles can be formed by over-firing at an elevated firing temperature, and can be prepared by using additives such as grain growth promoters that are useful for over-firing, or by changing the starting material.
[0189] For example, the sintering is performed at a temperature at which single particles can be formed. To form the single particles, the sintering should be performed at a higher temperature than that at which the secondary particles are produced. For example, when the precursor composition is the same, the sintering should be performed at a temperature about 30°C to 100°C higher than that at which the secondary particles are produced. The sintering temperature for forming the single particles may vary depending on the metal composition in the precursor. For example, when a high-content nickel (High-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 80 mol% or more is formed as a single particle, the sintering temperature may be about 700°C to 1000°C, preferably about 800°C to 950°C. When the sintering temperature satisfies the above range, a positive electrode active material including single particles having excellent electrochemical properties can be produced. When the sintering temperature is less than 790°C, a positive electrode active material including a lithium transition metal composite compound in the form of secondary particles can be produced, and when the sintering temperature exceeds 950°C, the sintering occurs excessively, the layered crystal structure is not formed well, and the electrochemical properties may be deteriorated.
[0190] In this specification, the term "single particle" is used to distinguish it from conventional secondary particles formed by agglomeration of tens to hundreds of primary particles, and is a concept that includes a single particle consisting of one primary particle and a pseudo-single particle form that is an agglomeration of 30 or less primary particles.
[0191] Specifically, the single particle in the present invention may be in the form of a single particle consisting of one primary particle or a pseudo-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.
[0192] In one embodiment of the present application, the lithium transition metal composite compound serving as the positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.
[0193] In the present invention, a single particle may be in the form of a single particle consisting of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and a secondary particle may be in the form of an aggregate of several hundred primary particles.
[0194] The lithium transition metal composite compound may further include secondary particles. The secondary particles refer to a form formed by agglomeration of primary particles, and can be distinguished from the concept of single particles including one primary particle, one single particle, or a pseudo-single particle form that is an agglomeration of 30 or less primary particles.
[0195] The particle diameter (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, and preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles is less than 0.05 m 2 / g~10m 2 / g, preferably 0.1m 2 / g~1m 2 / g, and more preferably 0.3m 2 / g~0.8m 2 / g.
[0196] In a further embodiment of the present application, the secondary particles are aggregates of primary particles, and the primary particles have an average particle size (D50) of 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of aggregates of several hundred primary particles, and the primary particles may have an average particle size (D50) of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.
[0197] When the average particle size (D50) of the primary particles is within the above range, a single particle positive electrode active material having excellent electrochemical properties can be formed. If the average particle size (D50) of the primary particles is too small, the number of agglomerates of the primary particles forming the lithium nickel oxide particles increases, and the effect of suppressing particle cracking during rolling decreases. If the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles becomes long, increasing resistance and causing a decrease in output characteristics.
[0198] According to a further embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, so that the single particles can have excellent particle strength even if they are formed with a small particle size, and thus the increase in fine particles in the electrode due to particle cracking can be mitigated, thereby improving the life characteristics of the battery.
[0199] In one embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles by 1 μm to 18 μm.
[0200] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm smaller, 1.5 μm to 15 μm smaller, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.
[0201] When the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, for example, when the above range is satisfied, the single particles can have excellent particle strength even if they are formed with a small particle size, and thus the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, resulting in an improvement in the life characteristics and energy density of the battery.
[0202] According to a further embodiment of the present application, the single particles are contained in an amount of 15 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material. The single particles may be contained in an amount of 20 parts by weight to 100 parts by weight, or 30 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material.
[0203] For example, the single particles may be included in an amount of 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more relative to 100 parts by weight of the positive electrode active material. The single particles may be included in an amount of 100 parts by weight or less relative to 100 parts by weight of the positive electrode active material.
[0204] When the single particles are contained in the above range, excellent battery characteristics can be exhibited in combination with the above-mentioned negative electrode material. In particular, when the single particles are 15 parts by weight or more, the increase in fine particles in the electrode due to particle cracking during rolling after electrode preparation can be mitigated, thereby improving the life characteristics of the battery.
[0205] In one embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the secondary particles may be 85 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 0 parts by weight or more relative to 100 parts by weight of the positive electrode active material.
[0206] When the above range is satisfied, the above-mentioned effect due to the presence of the single particle positive electrode active material can be maximized. When the secondary particle positive electrode active material is included, the component may be the same as or different from the components exemplified in the single particle positive electrode active material, and may refer to a form in which the single particles are aggregated.
[0207] In one embodiment of the present application, the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and still more preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0208] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0209] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.
[0210] The positive electrode binder plays a role in improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.
[0211] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular restrictions. In particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric substance may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.
[0212] In particular, by having a ceramic layer on the silicon-based negative electrode active material layer according to the present application, the ceramic layer formed on the separator can be eliminated or minimized, the thickness of the separator roll can be reduced, and the process and cost can be advantageously improved.
[0213] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.
[0214] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0215] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0216] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used because they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore these can be used more preferably.
[0217] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:
[0218] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purposes of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0219] One embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics, and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems. EXAMPLES
[0220] Below, preferred examples are presented to aid in understanding the present invention. However, these examples are intended to illustrate the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the appended claims.
[0221] <Example> <Production of negative electrodes> Example 1: Preparation of negative electrode Manufacture of negative electrode active material layer A negative electrode active material layer composition was prepared by mixing silicon-based active material Si (average particle size (D50): 5 μm), first conductive material, second conductive material, and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10. The negative electrode active material layer composition was prepared by adding distilled water as a solvent for forming a negative electrode slurry (solid concentration 28 wt%).
[0222] The first conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is carbon nanotubes.
[0223] The mixing method was as follows: the first conductive material, the second conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0224] The negative electrode slurry was applied at 3.00 mg / cm on both sides of a copper current collector (thickness: 15 μm) as a negative electrode current collector. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 23 μm).
[0225] Manufacturing of the ceramic layer The ceramic layer composition was prepared by mixing BaTiO3:Al2O3 as ceramics in a ratio of 20:80 based on 100 parts by weight of ceramics, and adding 20 parts by weight of PVdF as binder based on 100 parts by weight of ceramic layer composition. Then, the ceramic layer composition was prepared by adding it to acetone as a solvent (solid concentration 18% by weight).
[0226] Then, the ceramic layer composition was coated on the negative electrode active material layer, roll pressed, and dried in a vacuum oven at 60° C. for 10 hours to form a ceramic layer (thickness: 4 μm).
[0227] A negative electrode was manufactured in the same manner as in Example 1, except that the conditions for manufacturing the negative electrode active material layer and the ceramic layer were changed as follows.
[0228] [Table 1]
[0229] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).
[0230] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) and the positive electrode slurry was applied to both sides at 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).
[0231] An electrolyte was injected between the positive electrode and the negative electrode of Example 1 via a polyethylene separator, to prepare the secondary battery of Example 1.
[0232] The electrolyte was an organic solvent mixture of fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) in a volume ratio of 30:70, to which vinylene carbonate was added at 3 wt% based on the total weight of the electrolyte, and LiPF6 was added as a lithium salt at a concentration of 1M.
[0233] Except for using the negative electrodes of Examples 2 to 4 and Comparative Examples 1 to 6, secondary batteries were fabricated in the same manner as described above.
[0234] Experimental example 1: Evaluation of Monocell life The secondary battery manufactured as described above was subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention rate. The evaluation was performed at high temperature this time, in order to evaluate it in conjunction with the gas generation experiment in Experimental Example 2 described later. The secondary battery was subjected to 100 cycles of charging (1.0C CC / CV charging, 4.2V, 0.05C cut) and discharging (0.5C CC discharging, 3.0V cut) at 45°C, and then the capacity retention rate was confirmed.
[0235] The capacity retention rate at the 100th cell was evaluated according to the following formula, and the results are shown in Table 2 below.
[0236] Capacity retention rate (%) = {(discharge capacity at 100th cycle) / (discharge capacity at 1st cycle)} x 100
[0237] [Table 2]
[0238] Generally, life evaluation is carried out at room temperature, 25℃, but since gas due to side reactions is significantly generated only after a long life span, life evaluation was carried out at high temperatures where more gas is generated. At high temperatures, more reactions that form the SEI layer occur along with gas generation due to side reactions, so a significant difference could be confirmed, which was an evaluation that could more easily confirm the impact on ceramic particles.
[0239] From the life evaluation results in Table 2, it was confirmed that the performance of the Examples was superior to that of the Comparative Examples. Among the Examples, Example 1, which has an optimal ratio of BaTiO3 with small particles and Al2O3 with relatively large particles, showed the best performance, and it was confirmed in Example 4 that when the same ceramic composition is used and the thickness is thin, the resistance due to the thickness of the separator ceramic layer is reduced and some performance is increased.
[0240] In addition, the silicon content is increased in each of Examples 5 to 8, and the proportion of BaTiO3 is also increased accordingly. That is, in the case of Examples 5 to 8, as the content of the silicon-based active material increases, the conductive material and binder decrease, and it can be confirmed that some performance reduction occurred compared to Examples 1 to 4, but the capacity retention rate was very excellent compared to the comparative example.
[0241] Comparative Example 1 has a high BaTiO3 ratio and may be effective in removing gases, but because the particles are small, the packing density of the ceramic layer is increased, preventing ion migration and lowering ion conductivity, resulting in reduced life performance.
[0242] In Comparative Example 2, the proportion of BaTiO3 was relatively low and the resistance of the separator was low, but gas generation could not be effectively suppressed, and local gas traps were generated between the electrode and the separator, resulting in a decrease in life performance.
[0243] Comparative Example 3 is a single composition of BaTiO3, and is evaluated as having a high battery resistance due to the same effect as Comparative Example 1. Comparative Example 4, like Comparative Example 2, does not have a significant problem with resistance, but cannot suppress gas generation.
[0244] Comparative Examples 5 and 6 have the same composition as Comparative Example 1, but are thick or thin. When the thickness is thick like Comparative Example 5, the performance is reduced due to an increase in resistance, and when the thickness is very thin like Comparative Example 6, the absolute amount of BaTiO3 is very small, and it is judged that the tendency is similar to that of Comparative Example 2, where the BaTiO3 content is very low.
[0245] Experimental example 2: Gas analysis results (mono cell life after 100 cycles) After the mono cell evaluated above had reached 100 cycles of life, an analysis was carried out to confirm the gas generation status. Qualitative analysis was performed using a GC / MS device, and the 11 types of gases (H2, CO, CO2, CO3, CO4, CO5, CO6, CO7, CO8, CO9, CO10, CO11, CO12, CO13, CO14, CO15, CO16, CO17, CO18, CO19, CO21, CO22, CO23, CO36, CO37, CO38, CO39, CO41, CO42, CO43, CO51, CO52, CO53, CO54, CO55, CO56, CO57, CO58, CO59, CO66, CO67, CO68, CO69, CO69, CO70, CO71, CO72, CO73, CO74, CO75, CO75, CO76, CO77, 2、 CH4, C2H 2、 Analysis was performed for the following compounds (C2H4, C2H6, C3H6, C3H8, O2, and N2), and the results are shown in Table 3 below.
[0246] [Table 3]
[0247] As a result of the gas analysis, it was confirmed that the amount of gas generated was small in the examples with appropriate BaTiO3 content and appropriate thickness. It was also confirmed that Example 2 with a high BaTiO3 content and Example 3 with a large ceramic layer thickness and small composition but a large quantitative amount of BaTiO3 generated less gas than Example 1. Example 4 with a relatively thin thickness and BaTiO3 composition of 20 generated more gas than Examples 1 to 3.
[0248] The Comparative Examples generally show a higher gas generation amount than the Examples, but this is the result of the influence of the quantitative amount of BaTiO3. Comparative Examples 1, 3, and 5 correspond to cases where the composition content of BaTiO3 is high, the composition is a single component, or the thickness is large and the absolute amount is high, and in these cases, the total gas generation amount is similar to that of the Examples.
[0249] However, in the case of Comparative Examples 2, 4, and 6, when the Al2O3 content was high or was alone, or when the thickness was low and the amount of BaTiO3 was small, the amount of gas generated was high, which was determined to affect the life performance.
[0250] That is, as can be seen from Tables 2 and 3, the battery using the negative electrode according to the present application has an excellent life maintenance rate and is characterized by improved performance due to suppression of gas generation. [Explanation of symbols]
[0251] 10. Ceramic layer 20...Negative electrode active material layer 30 Negative electrode current collector layer
Claims
1. A negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a ceramic layer provided on a surface of the silicon-based negative electrode active material layer opposite to the surface facing the negative electrode current collector layer, The ceramic layer comprises a ceramic layer composition or a dried product thereof; The thickness of the ceramic layer is 0.5 μm or more and 10 μm or less, the ceramic layer composition comprises a ceramic and a binder; Based on 100 parts by weight of the ceramic, BaTiO 3 A negative electrode for a lithium secondary battery comprising 10 parts by weight or more and 50 parts by weight or less.
2. The ceramic is Al 2 O 3 , ZrO 2 , SiO 2 , TiO 2 , ZnO, BaTiO 3 , SrTiO 3 , CaCO 3 , CaO, CeO 2 , NiO, MgO, SnO 2 , Y 2 O 3 , Pb(Zr,Ti)O 3 (PZT), (Pb, La) (Zr, Ti) O 3 (PLZT), Pb(Mg 1/3 Nb 2/3 ) O 3 -PbTiO 3 (PMN-PT) and hafnia (HfO 2 2. The negative electrode for a lithium secondary battery according to claim 1, comprising at least one selected from the group consisting of:
3. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the binder is polyvinylidene fluoride (PVdF); or polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP).
4. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the ceramic is 60 parts by weight or more and 95 parts by weight or less, and the binder is 5 parts by weight or more and 40 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.
5. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein a surface of the ceramic layer opposite to the surface facing the silicon-based negative electrode active material layer is joined to lithium metal, and then the surface is left at 23° C. for 10 seconds to 2 minutes, after which the adhesive strength is 10 gf / 15 mm or more and 100 gf / 15 mm or less.
6. The silicon-based negative electrode active material layer includes a negative electrode active material layer composition, 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer composition comprises at least one selected from the group consisting of a silicon-based active material; a negative electrode conductive material; and a negative electrode binder.
7. 7. The negative electrode for a lithium secondary battery according to claim 6, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x ≦ 2), and the amount of the SiOx (x = 0) is 70 parts by weight or more based on 100 parts by weight of the silicon-based active material.
8. The negative electrode conductive material includes a sheet conductive material and a linear conductive material, 7. The negative electrode for a lithium secondary battery according to claim 6, wherein the sheet conductive material is contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
9. The negative electrode for a lithium secondary battery according to claim 6 , wherein the silicon-based active material is contained in an amount of 70 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.
10. Providing a negative electrode current collector layer; applying a negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a negative electrode active material layer; and applying a ceramic layer composition to a surface of the negative electrode active material layer opposite to the surface facing the negative electrode current collector layer to form a ceramic layer; A method for producing a negative electrode for a lithium secondary battery, comprising: The thickness of the ceramic layer is 0.5 μm or more and 10 μm or less, The ceramic layer composition comprises a ceramic and a binder; Based on 100 parts by weight of the ceramic, BaTiO 3 The negative electrode for a lithium secondary battery comprises 10 parts by weight or more and 50 parts by weight or less.
11. The method for manufacturing a negative electrode for a lithium secondary battery according to claim 10, further comprising the step of drying and rolling the ceramic layer composition to remove a solvent from the ceramic layer composition after the ceramic layer composition is applied.
12. pre-lithiating the negative electrode having the negative electrode active material layer and the ceramic layer formed on the negative electrode current collector layer; 11. The method of claim 10, wherein the prelithiation of the negative electrode comprises a lithium electrolytic plating process; a lithium metal transfer process; a lithium metal deposition process; or a stabilized lithium metal powder (SLMP) coating process.
13. Positive electrode; The negative electrode for a lithium secondary battery according to any one of claims 1 to 9; A separator disposed between the positive electrode and the negative electrode; and Electrolyte; A lithium secondary battery comprising:
Citation Information
Patent Citations
Anode for lithium-ion secondary battery and lithium-ion secondary battery
JP2010160984A
Electrode having porous coating layer, manufacturing method of the electrode and electrochemical element including the electrode
JP2016042467A
Composite negative electrode active material, method of manufacturing the same, negative electrode containing composite negative electrode active material, and lithium secondary battery including negative electrode
JP2016076487A
Anode for lithium ion battery
JP2009080971A